Full pulpotomy versus root canal therapy in mature teeth with irreversible pulpitis: a randomized controlled trial - Lina Zhu; Wei Liu; Xuetao Deng; Zhen Chen; Jiaxin Chen; Wenhao Qian (BMC, 2024)
Abstract Background Vital pulp therapy (VPT) is recommended as an alternative treatment to root canal therapy (RCT) for management of teeth with carious pulp exposure. This randomized clinical trial aimed to compare the outcomes and postoperative pain, and to evaluate the time and cost after full pulpotomy (FP) and RCT in mature molar teeth with irreversible pulpitis (IP). Methods A total of 160 mature molar teeth with IP were randomly divided into two treatment groups. The FP group (test group) was treated with FP using iRoot BP Plus by an endodontist, the RCT group (control group) was treated with RCT using iRoot SP as sealer by the same endodontist. Pain was recorded preoperatively and daily until day 7 postoperatively. The treatment time and cost were recorded. Clinical and radiographic assessments were collected, and pulp sensibility tests were done by electric pulp test (EPT) at 3-, 6-, 12- month postoperatively. Data were analyzed through chi-square test, Mann-Whitney U test, Fisher exact and independent t test. Results FP and RCT had comparable success rates (Clinical, 97.3% vs. 98.6%; radiographic, 93.3% vs. 94.6%) (P > 0.05). Pain levels decreased over time from day 1 to day 7 postoperative in both groups, and the FP group had larger reductions in pain intensity than RCT at day 1 (P < 0.05). In the FP group, there were 5, 3 and 3 unresponsive teeth with EPT at 3-, 6- and 12- month follow-ups, respectively. The treatment time and cost in the FP group were significantly lower than in the RCT group (P < 0.05). Conclusions FP could be an appropriate alternative treatment for management of mature teeth with IP in short follow-up. Trial registration The trial was registered in Chinese Clinical Trial Registry (ChiCTR2200063380 at 05/09/2022).